(untitled) (Editora Impacto Científico, 2025)
This article explores the theoretical and practical convergences between Waldorf Education (WP), developed by Rudolf Steiner, and contemporary Embodied Cognition (EC) approaches, with a special emphasis on the enactive approach. In an educational landscape seeking responses to the growing fragmentation of knowledge and socio-emotional challenges, this paper argues that WP, formulated in the early 20th century, not only anticipates fundamental EC principles—such as the centrality of embodied experience and cognition as situated action—but also proves to be a relevant praxis, validated by recent empirical research that correlates its artistic practices with competencies such as empathy (Martzog; Kuttner; Pollak, 2016) and its imaginative methods with the development of 21st-century skills (Tsortanidou; Daradoumis; Barberá, 2020). Through a theoretical review and analysis, this article examines how Steiner’s concepts of self-knowledge, human development, and pedagogical practice interact with Varela’s notions of enaction, structural coupling, and ethical know-how. The analysis reveals that both perspectives, although based on distinct theoretical foundations, converge notably in their contemplative epistemologies, which value the investigation of first-person experience as a path to knowledge, resulting in practical implications for understanding knowledge as an active process of co-creation between the subject and the world. It is concluded that the enactive approach offers a contemporary scientific framework that validates and enriches the understanding of Waldorf practices, while Steiner’s pedagogy offers a consolidated model of integral education that exemplifies the application of principles consonant with embodied cognition in practice.